Procedural Fluency from the View of Students of Mathematical Disposition Level through Google Classroom Assisted Learning - Rizki Nurhana Friantini; Rahmat Winata; Pradipta Annurwanda (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2021)
This study aims to describe procedural fluency in solving problems for students of the Mathematics Education Department at the STKIP Pamane Talino who obtain high and low mathematical dispositions through learning assisted by Google Classroom. This research is a qualitative research. The research subjects were two students in the third semester. Subjects were selected by purposive sampling. The research data was obtained by tests and interviews, and the validity of the data was obtained by using the triangulation method. The techniques of data analysis were trough: 1) classifying data into three indicators of the smoothness of the procedure; namely: a) implementing procedures appropriately, b) selecting and utilizing procedures, c) modifying procedures, then reducing data that are not included in the 3 indicators; 2) presenting data in a narrative; 3) concluding the procedural fluency obtained from the indicators of procedural fluency in problem-solving steps. The results of the high mathematical disposition analysis showed that students had excellent procedural skills because they could apply procedures appropriately. They were able to select and utilize procedures accurately, and were able to apply procedures properly and flexibly. In the other side, the students with low mathematical disposition, they had poor procedural skills because even though they were able to apply the procedure, choose, and use the procedure appropriately, they still could not comply with the procedure appropriately and accurately for they answered all the questions incorrectly.